The Need of Standardization of Individual Zakat Calculation in Indonesia - Dodik Siswantoro (Tazkia Islamic Finance and Business Review, 2012)
Objective – This research aimed to analyze zakat calculation practices from online providers. There are some differences in the calculation method, for example different treatment in zakatable deduction, types of income and zakat for business.Methods - Twenty-three zakat online calculators are analyzed and then grouped into a main category. A simulation model is employed by inputting several common assumptions.Results - The results showed that generally three zakat calculator become main providers and differences are still occur.Conclusion – This research showed that the calculation of zakat should be simpler, standardized, and may not cause double zakat counting for profession-zakat. Government should intervene to provide a single zakat calculation method that must be refereed by all zakat institutions and link it to tax system.Keywords: Zakat, accounting, calculation, online